Effects of Scaffolds on Urine- and Urothelial Carcinoma Tissue-Derived Organoids from Bladder Cancer Patients - Simon Walz; Paul Pollehne; Philipp Vollmer; Wilhelm K. Aicher; Arnulf Stenzl; Niklas Harland; Bastian Amend (Cells, 2023)
Organoids are three-dimensional constructs generated by placing cells in scaffolds to facilitate the growth of cultures with cell–cell and cell–matrix interactions close to the in vivo situation. Organoids may contain different types of cells, including cancer cells, progenitor cells, or differentiated cells. As distinct culture conditions have significant effects on cell metabolism, we explored the expansion of cells and expression of marker genes in bladder cancer cells expanded in two different common scaffolds. The cells were seeded in basement membrane extract (BME; s.c., Matrigel®) or in a cellulose-derived hydrogel (GrowDex®, GD) and cultured. The size of organoids and expression of marker genes were studied. We discovered that BME facilitated the growth of significantly larger organoids of cancer cell line RT112 (p < 0.05), cells from a solid tumor (p < 0.001), and a voiding urine sample (p < 0.001). Expression of proliferation marker Ki76, transcription factor TP63, cytokeratin CK20, and cell surface marker CD24 clearly differed in these different tumor cells upon expansion in BME when compared to cells in GD. We conclude that the choice of scaffold utilized for the generation of organoids has an impact not only on cell growth and organoid size but also on protein expression. The disadvantages of batch-to-batch-variations of BME must be balanced with the phenotypic bias observed with GD scaffolds when standardizing organoid cultures for clinical diagnoses.